2018
DOI: 10.3390/ijms19082394
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metagenomic Analysis of Rhizosphere Microbial Community Composition and Functional Potentials under Rehmannia glutinosa Consecutive Monoculture

Abstract: Consecutive monoculture of Rehmannia glutinosa, highly valued in traditional Chinese medicine, leads to a severe decline in both quality and yield. Rhizosphere microbiome was reported to be closely associated with the soil health and plant performance. In this study, comparative metagenomics was applied to investigate the shifts in rhizosphere microbial structures and functional potentials under consecutive monoculture. The results showed R. glutinosa monoculture significantly decreased the relative abundances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 59 publications
(94 reference statements)
0
24
0
Order By: Relevance
“…Thus the vigorous microbial metabolism and basic biological processes in the drought-treated samples may enhance peanut stress tolerance. In addition, higher signal transduction mechanism and defense mechanism were also detected in the drought-treated soil groups, which can confer high tolerance levels to stress and toxic compounds [42]. All in all, we speculate that these pathways in microbes may have implications for plant survival and drought tolerance to some extent, which need further research.…”
Section: Discussionmentioning
confidence: 86%
“…Thus the vigorous microbial metabolism and basic biological processes in the drought-treated samples may enhance peanut stress tolerance. In addition, higher signal transduction mechanism and defense mechanism were also detected in the drought-treated soil groups, which can confer high tolerance levels to stress and toxic compounds [42]. All in all, we speculate that these pathways in microbes may have implications for plant survival and drought tolerance to some extent, which need further research.…”
Section: Discussionmentioning
confidence: 86%
“…Commonly, the sign of positive and negative feedbacks is determined by the relationship between the microbe’s competitive ability in the rhizosphere and the effect of that microbe on that plant ( Bever et al, 2012 ). In the previous studies, we have found the genera of Pseudomonas and Lysobacter were significantly decreased, while the relative abundance of Fusarium was remarkably enriched in the replanted soil than that in the newly planted soil of R. glutinosa ( Wu et al, 2018a , b , c ). The large amount of R. glutinosa leaf and tuber residues present in the field after harvest likely resulted in rapid enrichment of catalpol in the soil rhizosphere ( Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 81%
“…These three strains were selected for further investigation since they were classified to the genera which were specifically profiled in the soil known to accumulate key R. glutinosa root metabolites through exudation (catalpol). Moreover, the genera Pseudomonas and Fusarium have been reported as the taxa significantly shifting in rhizosphere soils of R. glutinosa under various replantation regimes ( Wu et al, 2018a , b , c ). Pathogenic assay of these strains on R. glutinosa tissue culture seedlings showed that Rf1 ( F. oxysporum ) and Rf2 ( F. solani ) efficiently caused wilt disease in seedlings and a noticeable symptom was observed by 6 days following inoculation.…”
Section: Resultsmentioning
confidence: 99%
“…4D). Wu et al found that the relative abundance of Lysobacter, Pseudoxanthomonas, Pseudomonas and Burkholderia were significantly (p <0.05) increased in the newly cultivated soil of R. glutinosa compared to continuous monocropping soil [30]. Similarly, the abundance of beneficial bacteria such as Arthrobacter, Burkholderia, Rhodanobacter, and Sphingobacterium displayed a negatively correlation to the accumulation of toxic diisobutyl phthalate (DiBP) in monocropping soil of P. ginseng [12].…”
Section: Effect Of Soil Type On the Composition Of Rhizosphere Bactermentioning
confidence: 99%